2021
DOI: 10.3390/su13168962
|View full text |Cite
|
Sign up to set email alerts
|

An Officious Impact of Financial Innovations and ICT on Economic Evolution in China: Revealing the Substantial Role of BRI

Abstract: The Belt and Road Initiative removes regional barriers and brings communities closer together. In addition, ICT and financial innovation have helped transform the world into a big village and promoted economic growth. The study assessed the dynamic impact of ICT, economic globalization, and financial innovation on China’s economic growth. The study used quarterly data from 2000 to 2019 and used the ARDL model to determine long-term and short-term consequences. The results of the study show that ICT has a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 74 publications
2
8
0
Order By: Relevance
“…Based on the model of economic growth, the result for the LNICT indicator revealed a positive relationship and significant sign for China while a negative relationship and insignificant sign for Malaysia. The positive impact of LNICT on economic growth in China is linked with a previous study by Shehzad et al (2021). They found that countries with better ICT development can easily achieve a higher growth rate.…”
Section: Empirical Findingssupporting
confidence: 52%
“…Based on the model of economic growth, the result for the LNICT indicator revealed a positive relationship and significant sign for China while a negative relationship and insignificant sign for Malaysia. The positive impact of LNICT on economic growth in China is linked with a previous study by Shehzad et al (2021). They found that countries with better ICT development can easily achieve a higher growth rate.…”
Section: Empirical Findingssupporting
confidence: 52%
“…In the digital trend, financial innovation and the development of information and communication technology can promote sustainable economic growth in China (Shehzad et al, 2021). Digital Inclusive Finance, as a combination of the two, makes it easier for the people who were not enjoying the financial services before and were deprived of these.…”
Section: Introductionmentioning
confidence: 99%
“…Agreeableness positively impacts the intuitive and reliant decision-making styles ( El Othman et al, 2020 ). Employees with a low level of agreeableness are aggressive, oppositional, manipulative, callous, and strong-willed ( Shehzad et al, 2020 , 2021 ). Agreeable employees are more motivated to establish an interpersonal connection which contributes to a higher level of well-being and satisfaction ( Aydogmus et al, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%